(untitled) (The Journal of Psychology and Sociology, 2020)
The article is devoted to the place and role of intellectual capital in the formation of an intellectual nation. As a result of the implementation of the program «Intellectual nation-2020», implemented on the initiative of the head of state N. A. Nazarbayev, teachers of SKSU named after him. M. Auezov con- ducted a sociological study. The results of this research are disclosed in the article. The article describes the main goals of research work with the analysis of the level of students ‘ understanding of intellectual capital and views on it. In addition, all the tasks set in accordance with the main goal were given a basis based on the received answers to questions. The article considers intellectual capital as the fruit of an intellectual nation. from the point of view of students, a sociological analysis of information about intellectual capital, its contribution to the develop- ment of Kazakhstan was conducted. The purpose of the study was to identify the impact of intellectual capital on the formation of an intellectual nation and determine its prospects, and to develop an effective information and communica- tion program to influence the public. Key words: intellectual capital, human capital, intellectual nation, intellectual potential.